2013
DOI: 10.7150/ijbs.4918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visfatin Gene Polymorphism RS4730153 on Exercise-induced Weight Loss of Obese Children and Adolescents of Han Chinese

Abstract: Visfatin is a recently discovered adipokine that contributes to glucose and obesity-related conditions. This study investigates Visfatin RS4730153 polymorphism from the perspectives of its relations with glucose/lipid metabolism and its influence on the effects of exercise-induced weight loss. Eighty-eight obese Han Chinese children and adolescents were randomly selected from a 2008 Shanghai Weight Loss Summer Camp and were supervised to complete a 4 week aerobic exercise training program. Significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 14 publications
0
16
1
13
Order By: Relevance
“…Another recent non-RCT suggests that regular exercise has positive effects on obesity in Korean children by improving glycemic control and reducing body weight, thereby lowering visfatin levels (from 247.72±14.95 to 184.22±7.75; P <0.05). 60 Congruent with these findings, Lai et al 64 reported that a substantial decrease in HOMA-IR after exercise, might indicate that visfatin rs4730153 GG genotype (polymorphism), could possibly improve glucose metabolism in obese children and adolescents by enhancing insulin sensitivity to exercise. Due to the limited number of studies, ultimately, we did not conduct the meta-analysis on this hormone.…”
Section: Discussionmentioning
confidence: 94%
“…Another recent non-RCT suggests that regular exercise has positive effects on obesity in Korean children by improving glycemic control and reducing body weight, thereby lowering visfatin levels (from 247.72±14.95 to 184.22±7.75; P <0.05). 60 Congruent with these findings, Lai et al 64 reported that a substantial decrease in HOMA-IR after exercise, might indicate that visfatin rs4730153 GG genotype (polymorphism), could possibly improve glucose metabolism in obese children and adolescents by enhancing insulin sensitivity to exercise. Due to the limited number of studies, ultimately, we did not conduct the meta-analysis on this hormone.…”
Section: Discussionmentioning
confidence: 94%
“…The etiology of obesity seems to be associated with several factors, such as genetic polymorphisms (Lai et al, 2013;Boström et al, 2012), dysfunction of the hypothalamic hormone signaling related to satiety, appetite and hunger (Arruda et al, 2011;Thaler et al, 2010), increased release of proinfl ammatory adipokines by white adipose tissue, and positive energy balance, in which the high total calorie intake, mainly high intake of energy-dense foods rich in saturated fats (Borg et al, 2012), sugar and salt exceeds daily calorie requirement (Drewnowski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…O polimorfismo rs3801266 no gene da visfatina (NAMPT) foi relacionado com a adiposidade (IMC, circunferência abdominal e de quadril aumentados) em crianças indianas (Tabassum et al, 2012). Além disso, o genótipo GG da variante NAMPT rs4730153 foi associado com redução da trigliceridemia e aumento da sensibilidade à Insulina, em resposta ao exercício, em crianças obesas e adolescentes chinesas (Lai et al, 2013).…”
Section: Fatores Genéticos Da Obesidadeunclassified
“…Em outro estudo, o genótipo GG do polimorfismo NAMPT rs4730153 foi associado com redução de triglicérides e de glicemia e aumento da sensibilidade à insulina, em crianças e adolescentes obesos, em reposta a atividade física (Lai et al, 2013). Por outro lado, os polimorfismos do NAMPT (rs78411774 A>C, rs71564769 A>C e rs2302559 A>G) não foram relacionados a paramêtros antropométricos e de consumo de uma dieta natural em obesos (Stastny et al, 2013).…”
Section: Influência De Polimorfismos Genéticos Em Parâmetros Antropomunclassified